Case study on holistic assessment of the relationship between city and square - Turgut, Duygu (Journal of Architecture and Urbanism, 2020)
While the squares have been in the network of relations with the political, social and religious structure of the society since the early days of history, today, they have been associated with the cars, speed and technology in the process formed with the modernization movement. In some squares, there are tramways, public transportation routes and stops, and there are also motor vehicles. The squares have turned into places where there is a continuous flow with fast traffic except for waiting at the bus stops and railway station. With this change, our needs also changed, and with the introduction of motor vehicles in our lives, the squares remained as neglected urban spaces in an effort to create a transportation network. The use of the squares belongs to the period in which people have habit of being together, but now squares use belongs to a period in which we are not together even if we are side by side. Within the scope of this study, nowadays, approaches and practices for the squares that is an urban space in the world have been investigated. According to the results of sections, the criteria for evaluating the completeness of the city-square relationship in today’s conditions are set out in a table. The selected from the Trafalgar Square, Bryant Park and Taksim Square samples consecutively examined in the context of these criteria.